Proceeding of Proceedings of CHT-21 ICHMT International Symposium on Advances in Computational Heat Transfer 2021
DOI: 10.1615/ichmt.2021.cht-21.300
|View full text |Cite
|
Sign up to set email alerts
|

Transfer function estimation with SMC method for combined heat transfer: insensitivity to detail refinement of complex geometries

Abstract: The optimization of thermal transfers in engineering systems such as heat exchangers requires the analysis of the influence of heat sources upon the temperature at various positions of interest in the studied system. In order to achieve the resolution of the combined modes of heat transfer through these systems, their couplings and the complex 3D geometries involved need to be integrated with full accuracy. Recent developments in probabilistic formulations in the context of transient combined heat transfer (li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…• the power density throughout the solid phase ψ. 12 gathers all the computation times, illustrating that the benefits of using the stored propagation information, instead of running the Monte Carlo, is a computation time reduction by a factor 10 3 to 10 4 [22].…”
Section: Simulation Examplesmentioning
confidence: 99%
“…• the power density throughout the solid phase ψ. 12 gathers all the computation times, illustrating that the benefits of using the stored propagation information, instead of running the Monte Carlo, is a computation time reduction by a factor 10 3 to 10 4 [22].…”
Section: Simulation Examplesmentioning
confidence: 99%
“…For conciseness, the derivation of Eq. 3 and the integral formulation of θ R is not replicated but may be found in the work of Penazzi et al [24] and Bati et al [3] (and also in Tregan et al [29] for semi-transparent media). The absorbed solar irradiation is also unknown and its expression is given in Eq.…”
Section: Monte Carlo Algorithmmentioning
confidence: 99%
“…Indeed, this new approach has benefited practically from the computer graphics advances in image synthesis with MCM techniques [22] by the public release of efficient free software which guaranty independence between the MCM algorithm and the complex data representation while insuring fast access to data and the ability to manage large and complex three-dimensional (3D) geometry [32]. In addition, Penazzi et al [24] showed that the MCM algorithms developed to solve coupled heat transfers may be used to estimate and store propagators when heterogeneous and transient sources are known. This enables reusing propagators to evaluate their corresponding probe temperatures when the sources are different leading to a drastic reduction of computation time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This function can therefore be directly used at each iteration of the FDM algorithm, resulting in a significant reduction in computational time in comparison to a standard direct model resolution in which the MCM computation is performed at each iteration. The estimation of a function of physical quantities with the MCM was initially referred to as Inverse Monte Carlo and Symbolic Monte Carlo in the field of radiative transfer [6,7,13,27] and has only recently been applied to coupled heat transfer [35,34,33].…”
Section: Introductionmentioning
confidence: 99%